Axonal Length Determines Distinct Homeostatic Phenotypes in Human iPSC Derived Motor Neurons on a Bioengineered Platform. Issue 10 (18th February 2022) - Hagemann, Cathleen; Moreno Gonzalez, Carmen; Guetta, Ludovica; Tyzack, Giulia; Chiappini, Ciro; Legati, Andrea; Patani, Rickie; Serio, Andrea
Abstract: Stem cell‐based experimental platforms for neuroscience can effectively model key mechanistic aspects of human development and disease. However, conventional culture systems often overlook the engineering constraints that cells face in vivo. This is particularly relevant for neurons covering long range connections such as spinal motor neurons (MNs). Their axons extend up to 1m in length and require a complex interplay of mechanisms to maintain cellular homeostasis. However, shorter axons in conventional cultures may not faithfully capture important aspects of their longer counterparts. Here this issue is directly addressed by establishing a bioengineered platform to assemble arrays of human axons ranging from micrometers to centimeters, which allows systematic investigation of the effects of length on human axonas for the first time. This approach reveales a link between length and metabolism in human MNs in vitro, where axons above a "threshold" size induce specific molecular adaptations in cytoskeleton composition, functional properties, local translation, and mitochondrial homeostasis. The findings specifically demonstrate the existence of a length‐dependent mechanism that switches homeostatic processes within human MNs. The findings have critical implications for in vitro modeling of several neurodegenerative disorders and reinforce the importance of modeling cell shape and biophysical constraints with fidelity and precision in vitro. Abstract : In this study, Hagemann and co‐workers sought to understand the relationship between cellular size and function in human neurons, using a bioengineered microfabricated platform tailored to systematically study how axonal length affects neuronal homeostasis. They report a novel mechanism of length‐dependent adaptations that affects RNA‐translation and mitochondrial dynamics, which has implications for understanding basic neurobiology and modeling diseases in vitro.